Produção e composição dos polissacarídeos extracelulares de Planktothrix agardhii (Cyanobacteria) e suas relações com bactérias no reservatório de Barra Bonita - Meccheri, Fabricio Sebastiani (2010)
The organism Planktothrix agardhii belongs to one of the two most abundant genera in the world among the phytoplankton (the other is Microcystis sp.). Nevertheless, the genus Planktothrix is potentially toxic, producing microcystins and anotoxinas, which makes relevant knowledge of the biology of species that produce large biomass, as the case of P. agardhii, and the relationships with the communities that coexist with them. Knowledge of the composition of EPS was fundamental to the understanding of possible correlation with bacteria based on the use of EPS as a substrate. The EPS excreted by P. agardhii grown in axenic culture is a heteropolymer rich in glucose (17.04%), whose composition also have the monosaccharides: glucuronic acid 13.78%, 12.65% of fucose, from 10.95 n-acetyl galactosamine, 10.48% n-acetyl glucosamine, 7.78% of rhamnose, galactose 7.04%, 4.89% arabinose and 15.39% from other types of sugars. EPS is composed of only one fraction slightly acidic. The degradation of EPS by the bacteria in natural population of Barra Bonita reservoir started at 12 hours and was totally consumed on the 31st day of exposure. The degradation of the polysaccharide followed by gas chromatography showed a quick decrease in the amount of glucose followed by an increase in the same after the 12th day. As for glucuronic acid occurs primarily an increase in concentration, followed by a sharp decline after the 12th day. The other monosaccharides present degradation to a minimum concentration or were completely exhausted.